Application development on Android phone I - Kwok, Winona Kum Yee (2015)
As smartphones/devices are getting affordable, the number of users owning one is ever growing. It is amazing how a palm-sized device can do so much, increasing productivity, revolving around education, to connecting people living distances away, to sharing whatever comes to their mind on social media platforms with just a few taps. Due to the increasing number of users owning a smartphone, the demand and variety for mobile applications have grown as well. Therefore, the objective of this project is to design a multipurpose application that runs on Android powered devices. The application comes in handy in aiding user to overcome language barrier using the text to speech functionality. The application allows the use of camera to capture image and translate recognized words into text; the text could also be translated to speech. It also provides a barcode/QR code reader to decode barcode/QR code to get useful information. Another feature of the application is that it does speech recognition as well so it is able to translate speech to text. The waterfall approach was used to ensure that the overall development process of the application would be successful. Objectives of the project were identified after the requirement analysis. Thereafter, the design and implementation phase were conducted followed by the testing phase to ensure that integrated system with all functions work as expected. The project schedule was closely followed to ensure that tasks were completed on time. The development of the application including function implementation, integration, design and testing was done using the Android Development Tools (ADT). In conclusion, the objectives of the project were successfully accomplished and met on time. The functions of the application have met the end user requirements as well.